PENERAPAN ASAS KEBEBASAN BERKONTRAK DALAM PEMBUATAN PERJANJIAN BAKU (Studi Normatif Pada Perjanjian Pembiayaan Konsumen) - Dewi Hendrawati (Faculty of Law, Universitas Diponegoro, 2011)
Consumer's Financing Agency is one the non-bank financing institutions providing funding for people Legal contractual relationship between the agency and the consumer is started with the preparation of the contract. Consumer's contract is done in standardized written form which is prepared in advance by the agency. It means that all terms and conditions are made by the agency alone, then the consumer will only need to agree or reject upon the contract without capabilities of altering nor adding anything to the content of the contract. The standardized contract in general is not considering enough other party's interest so that it is being questioned whether it is still providing freedom to the contracting consumers. Consumer's contract making even it is made and prepared by the agency as one the contracting parties is still providing freedom to the consumers by signing or not signing it, freedom to choose the contracting parties and freedom of choosing legal protection. Nevertheless since it is made only by one party there is exoneraion clause that ,s potentially risking the consumers.